The salvage of nipple-areola complex using dimethyl sulfoxide: Salvage of NAC by DMSO - Ural, Alper; Karaduman, Harun; Halbony, Hala (Journal of Surgery and Medicine, 2025)
Nipple-areolar complex (NAC) necrosis is one of the most perilous minor complications in breast surgery. It is more common following mastectomy and less common after reduction mammoplasty. In the case study presented below, we share our approach and experience in NAC salvage following superomedial pedicle reduction mammoplasty. The application of dimethyl sulfoxide (DMSO) notably improved perfusion and played a crucial role in the salvage of NAC.